Near-zero cracking circulating fluidized bed fly ash-based road base material and formula design method thereof
By pretreating and modifying the circulating fluidized bed fly ash, the strength and stability problems in its application in road base materials are solved, and the "nearly zero" cracked road base materials are achieved, improving the durability and safety of the material.
Patent Information
- Application Number
- CN202510071880.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-16
AI Technical Summary
The application of circulating fluidized bed fly ash in road base gelling materials is limited, mainly because its chemical composition contains toxic heavy metals and unstable chemical components, resulting in insufficient strength, stability and durability of the material, which may lead to problems such as road cracks and settlement.
By pretreating alkali solution impregnation and high-temperature calcination of circulating fluidized bed fly ash, toxic heavy metals and unstable chemical components are removed, and calcium-aluminum hydrotalcite compounds are loaded through hydrothermal reactions to modify composite fly ash to improve gelation activity and crack resistance.
It effectively reduces the biomigability and toxicity of circulating fluidized bed fly ash, improves the gelling activity and crack resistance of the material, enhances the strength and durability of the road base material, and achieves the "near-zero" cracking effect.
Smart Images

Figure CN119822767A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of resource recycling, and in particular to a "near-zero" cracking circulating fluidized bed fly ash-based road base material and a formula design method thereof. Background Art
[0002] Circulating fluidized bed fly ash is a byproduct of circulating fluidized bed boilers in power plants. As the global demand for renewable energy increases, the amount of this byproduct is also increasing. Every year, the accumulation of circulating fluidized bed fly ash is about 120 million tons, which not only takes up a lot of storage space, but also puts significant pressure on the environment. Circulating fluidized bed boilers are designed to improve fuel combustion efficiency and reduce pollutant emissions. The application of in-furnace sulfur fixation technology is one of its major features. However, the application of this technology also leads to significant differences in the chemical composition of circulating fluidized bed fly ash and ordinary fly ash.
[0003] Compared with ordinary fly ash, the chemical composition of circulating fluidized bed fly ash contains more toxic heavy metal substances, such as lead, cadmium, arsenic and other heavy metals. The presence of these heavy metals not only increases the environmental risks of fly ash, but also may have potential impacts on human health. For example, lead and cadmium are widely considered to be heavy metals that are harmful to the nervous system and kidneys, and long-term exposure may cause serious health problems. In addition, circulating fluidized bed fly ash may also contain unstable chemical components, which may undergo chemical reactions under certain environmental conditions, further exacerbating its harm to the environment.
[0004] Due to the presence of these harmful components, the use of circulating fluidized bed fly ash in road base cementitious materials is limited, especially in engineering applications where material stability and durability need to be ensured. In road construction, the strength, stability and durability of materials are key factors to ensure the service life and safety of roads. The chemical characteristics of circulating fluidized bed fly ash make its performance in these aspects unsatisfactory, which may cause cracks, settlement and other problems during road use, thus affecting the safety and service life of the road.
[0005] Although circulating fluidized bed fly ash has certain recycling value in some areas, such as being a partial substitute for cement or used in certain specific soil improvements, its application in cementitious materials such as road construction is strictly limited. Therefore, it is urgent to improve its safety and application performance through technological innovation and improvement of treatment processes.
[0006] Chinese patent document CN110282888A proposes a circulating fluidized bed fly ash-based auxiliary cementitious material, and its preparation method and application. The cementitious material prepared by using circulating fluidized bed fly ash, slag and water slag solves the technical problems of low early strength, slump loss and high cost of cement concrete prepared by existing auxiliary cementitious materials. The circulating fluidized bed fly ash-based auxiliary cementitious material prepared by the patent can be used to make cement, or replace part of the cement to prepare high-strength cement concrete, which is beneficial to improve the workability and durability of concrete, while reducing the use of cement clinker, thereby reducing carbon emissions, but the crack resistance of the prepared cementitious material still needs to be improved. Summary of the invention
[0007] In view of the deficiencies of the prior art, the object of the present invention is to provide a circulating fluidized bed fly ash-based road base material and a formulation design method thereof.
[0008] In order to achieve the above object, the present invention adopts the following technical solutions:
[0009] In the first aspect, the present invention provides a "near-zero" cracking circulating fluidized bed fly ash-based road base material, which includes the following raw materials, measured by weight: 20-35 parts of red mud, 20-30 parts of ordinary fly ash, 5-10 parts of slaked lime, 30-50 parts of coal gangue aggregate, and 20-80 parts of circulating fluidized bed fly ash-based composite material.
[0010] The preparation method of the circulating fluidized bed fly ash-based composite material is as follows:
[0011] S1, adding circulating fluidized bed fly ash into an alkaline solution for impregnation treatment, followed by centrifugation, drying, and calcining in an air atmosphere to obtain pretreated fly ash;
[0012] S2, dissolving calcium nitrate, aluminum nitrate and urea in water, mixing them evenly, then adding pretreated fly ash thereto, heating and stirring to react, and after the reaction is completed, filtering, washing and drying to obtain composite fly ash;
[0013] S3, dispersing the composite fly ash in an ethanol aqueous solution, then adding vinyltrimethoxysilane thereto, stirring for 2-5 hours, then filtering, washing, and drying to obtain a double-bond modified composite material;
[0014] S4, dispersing the double-bond modified composite material in an organic solvent, then adding butadiene, styrene and benzoyl peroxide thereto, heating and stirring to react, and after the reaction is completed, filtering, washing and drying to obtain a circulating fluidized bed fly ash-based composite material.
[0015] Specifically, in step S1, the alkaline solution is a NaOH solution or a KOH solution; the concentration of the alkaline solution is 0.5-2 mol / L;
[0016] The immersion time is 2-4 hours, for example, 2 hours, 2.5 hours, 3 hours, 3.5 hours, and 4 hours can be selected;
[0017] The calcination temperature is 800-900°C, for example, 800°C, 810°C, 820°C, 830°C, 840°C, 850°C, 860°C, 870°C, 880°C, 890°C, and 900°C can be selected; the calcination time is 2-4h, for example, 2h, 2.5h, 3h, 3.5h, and 4h can be selected; but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0018] Specifically, in step S2, the mass ratio of calcium nitrate, aluminum nitrate, urea and pretreated fly ash is 3-5:2-4:6-8:10-15.
[0019] In step S2, the temperature of the heating and stirring reaction is 70-85°C, for example, 70°C, 72°C, 74°C, 75°C, 76°C, 78°C, 80°C, 82°C, 85°C can be selected; the time of the heating and stirring reaction is 12-18h, for example, 12h, 13h, 14h, 15h, 16h, 17h, 18h can be selected; but it is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0020] Specifically, in step S3, the mass ratio of composite fly ash and vinyltrimethoxysilane is 8-12:1-3, for example, 8:1, 8:2, 8:3, 10:1, 10:2, 10:3, 12:1, 12:2, 12:3 can be selected, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0021] Specifically, in step S4, the mass ratio of the double bond modified composite material, butadiene, styrene and benzoyl peroxide is 10-15:3-4:3-5:0.5-1.
[0022] In step S4, the temperature of the heating and stirring reaction is 60-80°C, for example, 60°C, 65°C, 70°C, 75°C, and 80°C can be selected; the time of the heating and stirring reaction is 3-5h, for example, 3h, 3.5h, 4h, 4.5h, and 5h can be selected, but it is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0023] In a second aspect, the present invention provides a method for preparing a "near-zero" cracking circulating fluidized bed fly ash-based road base material, comprising the following steps: placing red mud, ordinary fly ash, slaked lime, coal gangue aggregate and the above-mentioned circulating fluidized bed fly ash-based composite material in a blast drying oven and drying to constant weight, passing through a 200-mesh sieve after ball milling, and then mixing the above-mentioned raw materials evenly, subsequently adding water, stirring for 3-5 minutes, making a test piece, and after demolding with a demolding machine, placing it in a curing box to cure to the corresponding age, thereby obtaining a circulating fluidized bed fly ash-based road base material.
[0024] In a third aspect, the present invention also provides a method for designing a formula of a "near-zero" cracking circulating fluidized bed fly ash-based road base material, comprising the following steps:
[0025] 1) The total number of red mud, ordinary fly ash, slaked lime and coal gangue aggregate is 100 parts. The above-mentioned circulating fluidized bed fly ash-based composite material is used as a variable to configure four types of road base materials. The dosage of the circulating fluidized bed fly ash-based composite material is 0, 30, 50 and 80 parts respectively, which are recorded as proportions M0, M3, M5 and M8;
[0026] 2) Assemble two polyamide inner molds into a dumbbell-shaped cavity, cover the outside with four cast iron dumbbell-shaped outer molds, put the dumbbell-shaped cast iron pad into the bottom of the cavity after assembly, move the assembled test mold into an environmental box, the temperature of the environmental box is regulated by a temperature and humidity controller, load four types of road base materials, and maintain for 4 hours after static pressure molding, then remove the cast iron outer mold to obtain the test piece and the inner mold, and fix the polyamide inner bottom mold at both ends of the inner mold;
[0027] 3) Fix the specimen and inner mold on the UTM testing machine in the vertical direction through the upper and lower clamps. The upper end of the UTM clamp is connected to the force sensor and displacement sensor to measure the displacement s of the specimen. i Heli F i To conduct real-time testing, the allowable displacement range s of the specimen, the set temperature and humidity of the environment T / ω, and the data collection time interval t are input into the computer program connected to the UTM;
[0028] 4) Turn on the UTM test equipment and perform displacement s i Heli F i Real-time testing, temperature and humidity T0 and ω i In real-time testing, when the real-time displacement monitored by the displacement sensor reaches the set value s, the UTM testing machine pulls the specimen back to its initial position, so that the deformation of the specimen remains at 0. i Calculate the real-time strain and accumulate it to obtain the accumulated strain ε of autogenous shrinkage and creep shrinkage ij , the calculation formula is as follows: i Calculate real-time stress σ i , the calculation formula is as follows:
[0029] ε ij =(s i +s·j) / L (1)
[0030] σ i =F i / S (2)
[0031] Where j is the number of times the UTM testing machine stretches the specimen; L is the specimen length, in m, and S is the cross-sectional area of the specimen, in m 2 ;
[0032] 5) The stress-strain results of the ratios M0, M3, M5 and M8 are statistically analyzed, and the stress is denoted as σ i 0 , σ i 3 , σ i 5 , σ i 8 , the accumulated strain is denoted as ε ij 0 , ε ij 3 , ε ij 5 , ε ij 8 , the stresses at cracking are σ c 0 , σ c 3 , σ c 5 , σ c 8 , the cracking time is t c 0 ,t c 3 ,t c 5 ,t c 8 The least square method is used to calculate the real-time stress σ before cracking of the road base after adding circulating fluidized bed fly ash-based composite materials with different dosages ω i and the accumulated strain ε ij , cracking stress after cracking σ c and cracking time t c , as shown in formulas (3) to (6),
[0033]
[0034] Where ω is the proportion of the circulating fluidized bed fly ash-based composite material to the total amount of red mud, ordinary fly ash, slaked lime and coal gangue aggregate;
[0035] 6) Draw the curves l0, l3, l5, and l8 of the real-time stress-time variation of the M0, M3, M5, and M8 specimens; the maximum compressive stress in the expansion stage is σ s 0 , σ s 3 , σ s 5 , σ s 8 , after heating up and then cooling down to the pouring temperature, the room temperature stress σ0 0 ,σ0 3 ,σ0 5 ,σ0 8 , corresponding to the stress reserve value ω σ 0 ,ω σ 3 ,ω σ 5 ,ω σ 8 Calculate them separately, as shown in formula (7). The larger the value, the better the crack resistance of the road base material.
[0036]
[0037] 7) According to the maximum compressive stress, room temperature stress, cracking stress and corresponding cracking time, stress reserve value index of the road base composed of circulating fluidized bed fly ash-based composite materials in the expansion stage with different dosages, the dosage of circulating fluidized bed fly ash-based composite materials is determined in combination with the road base use environment and performance requirements.
[0038] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0039] (1) The present invention pre-treats the circulating fluidized bed fly ash by immersing it in an alkaline solution and calcining it at high temperature, which can effectively remove toxic heavy metal substances and unstable chemical components contained in the circulating fluidized bed fly ash, reduce its biomobility and toxicity in the environment, and at the same time improve the activity of the circulating fluidized bed fly ash through alkaline activation treatment.
[0040] (2) The present invention loads calcium aluminum hydrotalcite compounds on the surface and in the pore structure of circulating fluidized bed fly ash through a hydrothermal reaction, which can reduce the water demand ratio of the circulating fluidized bed fly ash and improve its gelling activity; the calcium aluminum hydrotalcite compounds have good fluidity, can improve the fluidity of the slurry, improve the microstructure of the material, form a more uniform material matrix, reduce the generation of cracks, and thus enhance the anti-cracking performance of the matrix material.
[0041] (3) The present invention utilizes vinyl trimethoxysilane to treat the composite fly ash, introduces a double bond structure on its surface, and then reacts with butadiene and styrene to introduce a butadiene-styrene polymer structure on the composite fly ash. The butadiene-styrene polymer structure forms a three-dimensional network structure, which can be interwoven with the red mud hydration product, thereby improving the mechanical properties of the material, such as compressive strength and flexural strength; at the same time, the butadiene-styrene polymer structure also has good elasticity and toughness, and works together with the calcium-aluminum hydrotalcite compound to make the road base material have excellent crack resistance.
[0042] (4) The deformation monitored in the formula design provided by the present invention includes shrinkage and creep, which is more in line with the factors that cause road base cracking under actual conditions, and has high measurement accuracy, enhanced anti-interference ability, and simple operation. By designing the composition of the road base material adding circulating fluidized bed fly ash-based composite materials, the dosage is optimized to form a "near-zero" cracking road base material. In addition, the maximum stress in the expansion stage, room temperature stress value, cracking stress and corresponding cracking time, stress reserve value and other key indicators can be calculated based on the monitoring data, and the shrinkage and cracking behavior of the road base can be evaluated from different angles. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 A schematic diagram of the structure of the test equipment provided by the present invention;
[0044] Figure 2 A schematic diagram of the structure of the inner mold of the test device provided by the present invention;
[0045] Figure 3 A schematic diagram of the structure of the outer mold of the testing device provided by the present invention;
[0046] Figure 4 A structural schematic diagram of the location of the temperature and humidity sensor in the test equipment provided by the present invention;
[0047] Figure 5 is a curve diagram showing the relationship between temperature and test time in Example 4;
[0048] Figure 6 is a curve diagram showing the relationship between stress and test time in Example 4;
[0049] Figure 7 The present invention provides a flow chart of the road base material formulation design method.
[0050] Description of reference numerals:
[0051] 1- environmental chamber, 2- UTM testing machine, 3- displacement sensor, 4- force sensor, 5- upper chuck, 6- lower chuck, 7- inner mold, 71- inner side mold, 72- inner bottom mold, 8- outer mold, 81- outer side mold, 82- outer side mold, 83- outer mold pad, 9- temperature and humidity sensor, 10- temperature and humidity controller. DETAILED DESCRIPTION
[0052] The present invention is further described in detail below through specific preferred embodiments, but the present invention is not limited to the following embodiments.
[0053] It should be noted that, unless otherwise specified, the chemical reagents involved in the present invention were purchased through commercial channels.
[0054] The raw materials used are introduced as follows: red mud is Bayer red mud, which comes from Shanxi Huaxing Aluminum Co., Ltd. in Xiaoyi City, Shanxi Province; ordinary fly ash is first-class fly ash, which comes from Hebei Huishun Mining Co., Ltd.; slaked lime comes from Yingge Mining Co., Ltd. in Fenyi County, Yichun City, Jiangxi Province; coal gangue aggregate comes from Shanxi Pingshuo Coal Gangue Power Generation Co., Ltd.; circulating fluidized bed fly ash comes from Shanxi Pingshuo Coal Gangue Power Generation Co., Ltd., and its chemical composition is: CaO content is 31.56%, SiO2 content is 29.34%, Al2O3 content is 12.57%, Fe2O3 content is 6.86%, MgO content is 0.96%, K2O content is 0.92%, Na2O content is 0.39%, and f-CaO content is 2.4%.
[0055] Example 1
[0056] A method for preparing a "near-zero" cracking circulating fluidized bed fly ash-based road base material comprises the following steps:
[0057] 28 parts of red mud, 26 parts of ordinary fly ash, 6 parts of slaked lime, 40 parts of coal gangue aggregate and 40 parts of circulating fluidized bed fly ash-based composite materials were placed in a blast drying oven and dried to constant weight, and then passed through a 200-mesh sieve after ball milling. Then, the above raw materials were mixed evenly, and then 15 parts of water were added and stirred for 5 minutes to make a test piece. After demoulding with a demoulding machine, it was placed in a curing box for curing, and a circulating fluidized bed fly ash-based road base material was obtained;
[0058] The preparation method of the circulating fluidized bed fly ash-based composite material is as follows:
[0059] S1. Add 20 g of circulating fluidized bed fly ash into 150 mL of 1 mol / L NaOH solution, soak for 3 h, then centrifuge, dry, and calcine at 800 °C in air atmosphere for 4 h to obtain pretreated fly ash;
[0060] S2, dissolving 3g of calcium nitrate, 2g of aluminum nitrate and 6g of urea in 100mL of water, mixing evenly, then adding 10g of pretreated fly ash thereto, heating and stirring at 70°C for 18h, after the reaction is completed, filtering, washing and drying to obtain composite fly ash;
[0061] S3, dispersing 8 g of composite fly ash in 100 mL of 75 wt% ethanol aqueous solution, then adding 1 g of vinyltrimethoxysilane thereto, stirring for 3 h, then filtering, washing, and drying to obtain a double-bond modified composite material;
[0062] S4. Disperse 10 g of the double-bond modified composite material in 150 mL of the organic solvent DMF, then add 3 g of butadiene, 3 g of styrene and 0.5 g of benzoyl peroxide, heat and stir at 60°C to react for 5 hours. After the reaction is completed, filter, wash and dry to obtain a circulating fluidized bed fly ash-based composite material.
[0063] Example 2
[0064] A method for preparing a "near-zero" cracking circulating fluidized bed fly ash-based road base material comprises the following steps:
[0065] 30 parts of red mud, 25 parts of ordinary fly ash, 5 parts of slaked lime, 40 parts of coal gangue aggregate and 20 parts of circulating fluidized bed fly ash-based composite material were placed in a blast drying oven and dried to constant weight, and then passed through a 200-mesh sieve after ball milling. Then, the above raw materials were mixed evenly, and then 10 parts of water were added and stirred for 5 minutes to make a test piece. After demoulding with a demoulding machine, it was placed in a curing box for curing, and a circulating fluidized bed fly ash-based road base material was obtained;
[0066] The preparation method of the circulating fluidized bed fly ash-based composite material is as follows:
[0067] S1. Add 20 g of circulating fluidized bed fly ash into 150 mL of 1 mol / L NaOH solution, soak for 3 h, then centrifuge, dry, and calcine at 800 °C in air atmosphere for 4 h to obtain pretreated fly ash;
[0068] S2, dissolving 5g of calcium nitrate, 4g of aluminum nitrate and 8g of urea in 100mL of water, mixing evenly, then adding 15g of pretreated fly ash thereto, heating and stirring at 85°C for 12h, after the reaction is completed, filtering, washing and drying to obtain composite fly ash;
[0069] S3, dispersing 12 g of composite fly ash in 100 mL of 75 wt% ethanol aqueous solution, then adding 3 g of vinyltrimethoxysilane thereto, stirring for 3 h, then filtering, washing, and drying to obtain a double-bond modified composite material;
[0070] S4. Disperse 15 g of the double-bond modified composite material in 150 mL of the organic solvent DMF, then add 4 g of butadiene, 5 g of styrene and 1 g of benzoyl peroxide, heat and stir to react at 80°C for 3 h, and after the reaction is completed, filter, wash and dry to obtain a circulating fluidized bed fly ash-based composite material.
[0071] Example 3
[0072] A method for preparing a "near-zero" cracking circulating fluidized bed fly ash-based road base material comprises the following steps:
[0073] 35 parts of red mud, 25 parts of ordinary fly ash, 10 parts of slaked lime, 30 parts of coal gangue aggregate and 80 parts of circulating fluidized bed fly ash-based composite material were placed in a blast drying oven and dried to constant weight, and then passed through a 200-mesh sieve after ball milling. Then, the above raw materials were mixed evenly, and then 20 parts of water were added and stirred for 5 minutes to make a test piece. After demoulding with a demoulding machine, it was placed in a curing box for curing, and a circulating fluidized bed fly ash-based road base material was obtained;
[0074] The preparation method of the circulating fluidized bed fly ash-based composite material is as follows:
[0075] S1. Add 20 g of circulating fluidized bed fly ash into 150 mL of 1 mol / L NaOH solution, soak for 3 h, then centrifuge, dry, and calcine at 800 °C in air atmosphere for 4 h to obtain pretreated fly ash;
[0076] S2, dissolving 4g of calcium nitrate, 2g of aluminum nitrate and 7g of urea in 100mL of water, mixing evenly, then adding 12g of pretreated fly ash thereto, heating and stirring at 80°C for 15h, after the reaction is completed, filtering, washing and drying to obtain composite fly ash;
[0077] S3, dispersing 10 g of composite fly ash in 100 mL of 75 wt% ethanol aqueous solution, then adding 2 g of vinyltrimethoxysilane thereto, stirring for 3 h, then filtering, washing, and drying to obtain a double-bond modified composite material;
[0078] S4. Disperse 12 g of the double-bond modified composite material in 150 mL of organic solvent DMF, then add 3.5 g of butadiene, 4 g of styrene and 0.8 g of benzoyl peroxide, heat and stir at 70°C for 4 hours, and after the reaction is completed, filter, wash and dry to obtain a circulating fluidized bed fly ash-based composite material.
[0079] Comparative Example 1
[0080] A method for preparing a circulating fluidized bed fly ash-based road base material comprises the following steps:
[0081] 28 parts of red mud, 26 parts of ordinary fly ash, 6 parts of slaked lime, 40 parts of coal gangue aggregate and 40 parts of circulating fluidized bed fly ash-based composite materials were placed in a blast drying oven and dried to constant weight, and then passed through a 200-mesh sieve after ball milling. Then, the above raw materials were mixed evenly, and then 15 parts of water were added and stirred for 5 minutes to make a test piece. After demoulding with a demoulding machine, it was placed in a curing box for curing, and a circulating fluidized bed fly ash-based road base material was obtained;
[0082] The preparation method of the circulating fluidized bed fly ash-based composite material is as follows:
[0083] S1. Add 20 g of circulating fluidized bed fly ash into 150 mL of 1 mol / L NaOH solution, soak for 3 h, then centrifuge, dry, and calcine at 800 °C in air atmosphere for 4 h to obtain pretreated fly ash;
[0084] S2, dispersing 8 g of pretreated fly ash in 100 mL of 75 wt% ethanol aqueous solution, then adding 1 g of vinyltrimethoxysilane thereto, stirring for 3 h, then filtering, washing, and drying to obtain double bond modified fly ash;
[0085] S3. Disperse 10 g of double-bond modified fly ash in 150 mL of organic solvent DMF, then add 3 g of butadiene, 3 g of styrene and 0.5 g of benzoyl peroxide, heat and stir at 60°C for 5 h, and after the reaction is completed, filter, wash and dry to obtain a circulating fluidized bed fly ash-based composite material.
[0086] Compared with Example 1, in Comparative Example 1, no calcium aluminum hydrotalcite compound is loaded on the pretreated fly ash.
[0087] Comparative Example 2
[0088] A method for preparing a circulating fluidized bed fly ash-based road base material comprises the following steps:
[0089] 28 parts of red mud, 26 parts of ordinary fly ash, 6 parts of slaked lime, 40 parts of coal gangue aggregate and 40 parts of circulating fluidized bed fly ash-based composite materials were placed in a blast drying oven and dried to constant weight, and then passed through a 200-mesh sieve after ball milling. Then, the above raw materials were mixed evenly, and then 15 parts of water were added and stirred for 5 minutes to make a test piece. After demoulding with a demoulding machine, it was placed in a curing box for curing, and a circulating fluidized bed fly ash-based road base material was obtained;
[0090] The preparation method of the circulating fluidized bed fly ash-based composite material is as follows:
[0091] S1. Add 20 g of circulating fluidized bed fly ash into 150 mL of 1 mol / L NaOH solution, soak for 3 h, then centrifuge, dry, and calcine at 800 °C in air atmosphere for 4 h to obtain pretreated fly ash;
[0092] S2. Dissolve 3g of calcium nitrate, 2g of aluminum nitrate and 6g of urea in 100mL of water and mix well. Then add 10g of pretreated fly ash and heat and stir at 70°C to react for 18h. After the reaction is completed, filter, wash and dry to obtain a circulating fluidized bed fly ash-based composite material.
[0093] Compared with Example 1, Comparative Example 2 does not load the styrene-butadiene polymer structure.
[0094] The road base materials prepared in Examples 1-3 and Comparative Examples 1-2 were subjected to standard curing, in which the standard curing was carried out in a standard curing room at a temperature of 20±1°C and a humidity RH value of >95%. The unconfined compressive strength and splitting tensile strength of the samples were tested at 7d and 28d of curing according to JTG E51-2009 "Test Procedure for Inorganic Binder Stabilized Materials for Highway Engineering".
[0095] The test results are shown in Table 1:
[0096] Table 1
[0097]
[0098] It can be seen from Table 1 that, compared with Comparative Examples 1-2, the sample material prepared by modifying the circulating fluidized bed fly ash in the present invention has more excellent mechanical properties.
[0099] In addition, the present invention also provides a method for designing a formula of a "near-zero" cracking circulating fluidized bed fly ash-based road base material, which will be further described below in conjunction with specific embodiments.
[0100] Example 4
[0101] S1. Design the initial mix ratio of road base materials: 28 parts of red mud + 26 parts of fly ash + 6 parts of slaked lime + 40 parts of coal gangue aggregate, add 0, 30, 50 and 80 parts of circulating fluidized bed fly ash-based composite materials respectively, mix the above raw materials with 15 parts of water evenly, make test pieces, and obtain 4 types of road base materials, recorded as mix ratios M0, M3, M5 and M8.
[0102] S2, such as Figure 1 to Figure 4As shown, the test equipment of the present invention includes a UTM test machine 2, a force sensor 4, a displacement sensor 3, an upper chuck 5, a lower chuck 6, a temperature and humidity controller 10, and a test mold. The lower part of the UTM test machine 2 is connected to the displacement sensor 3, the lower part of the displacement sensor 3 is connected to the force sensor 4, the lower part of the force sensor 4 is connected to the upper chuck 5, the lower chuck 6 is consolidated with the bottom of the environmental chamber 1, the upper and lower chucks 5 and 6 clamp the test piece to ensure that its position is located in the middle of the environmental chamber, and the upper chuck 5 adjusts the position of the upper part of the test piece through the UTM test machine 2. The test mold includes an inner mold 7 and an outer mold 8. The material of the inner mold 7 is polyurethane, and it consists of two inner side molds 71 and two upper and lower inner bottom molds 72, both of which are 10 mm thick. The inner bottom molds 72 are placed on both sides of the inner mold 71 and are fixed by clamps after demoulding. The material of the outer mold 8 is cast iron, and it consists of two outer side molds 81, two outer side molds 82 and two outer mold pads 83, both of which are 16 mm thick. The heights of the outer side molds 81 and 82 are 140 mm, and the height of the outer mold pad 83 is 20 mm. The outer mold 81 and 82 are spliced to form a dumbbell-shaped hollow structure, the outer mold pad 83 is placed at the bottom, and the inner mold 71 is placed in the hollow structure. After the road base material fills the inner mold 7, the outer mold pad is placed. The assembled test mold is moved into the environmental box 1. The temperature of the environmental box 1 is regulated by the temperature and humidity controller 10. The temperature is set to the maintenance temperature Tc. The temperature and humidity sensor 9 is pre-buried in the test mold. Four types of road base materials are loaded. The test piece is dumbbell-shaped, with a thickness of 50 mm and a total length of 300 mm. The middle section is 200 mm long and 50 mm wide. The protruding lengths at both ends are 25 mm and 100 mm wide. The middle is transitioned by a 1 / 4 arc with a radius of 25 mm. After static pressure molding, it is cured for 4 hours. Then, the cast iron outer mold 8 is removed to obtain the test piece and the inner mold 71, and then the inner bottom mold 72 is fixed to both ends of the inner mold 71.
[0103] S3, fix the specimen and the inner mold 7 on the UTM testing machine 2 in the vertical direction through the upper clamp 5 and the lower clamp 6, and connect the force sensor 4 and the displacement sensor 3 at the upper end of the UTM clamp 5 to measure the displacement s of the specimen. i Heli F i To conduct a real-time test, the computer program connected to the UTM testing machine 2 is input with information such as the allowable displacement range s of the specimen, the ambient temperature and humidity T / ω, and the data collection time interval t.
[0104] S4, start the UTM testing machine 2, and perform displacement s i Heli F i Real-time testing, temperature and humidity T0 and ω i In real-time testing, when the real-time displacement monitored by the displacement sensor 3 reaches the set value s, the UTM testing machine 2 pulls the specimen back to its initial position, so that the deformation of the specimen remains at 0. iCalculate the real-time strain and accumulate it to obtain the accumulated strain ε of autogenous shrinkage and creep shrinkage ij , the calculation formula is as follows: i Calculate real-time stress σ i , the calculation formula is as follows:
[0105] ε ij =(s i +s·j) / 0.2 (1)
[0106] σ i =F i / 0.0025 (2)
[0107] Where j is the number of times the UTM testing machine stretches the specimen.
[0108] S5. The stress-strain results of the ratios M0, M3, M5 and M8 are statistically analyzed, and the stress is recorded as σ i 0 , σ i 3 , σ i 5 , σ i 8 , the accumulated strain is denoted as ε ij 0 , ε ij 3 , ε ij 5 , ε ij 8 , the stresses at cracking are σ c 0 =-405kPa, σ c 3 =-355kPa, σ c 5 =-280kPa, σ c 8 =-224kPa, the cracking time is t c 0 =172h, t c 3 =184h, t c 5 =192h, t c 8 = 216h, the least square method is used to calculate the real-time stress σ before cracking of the road base after adding circulating fluidized bed fly ash-based composite materials with different dosages ω i and the accumulated strain ε ij , cracking stress after cracking σ c and cracking time t c , as shown in formulas (3) to (6),
[0109]
[0110] S6. Draw curves of the temperature-time variation and stress-time variation of the M0, M3, M5 and M8 specimens, such as Figure 5-6 As shown; Figure 5 It is the temperature change after pouring the sample, which is used to describe the change of hydration heat. The change of heating rate can reflect the risk of temperature cracking, and the heating and cooling time nodes can be used to Figure 7 The maximum compressive stress in the expansion stage is σ s 0 =200kPa,σ s 3 =280kPa,σ s 5 =390kPa,σ s 8 =520kPa, room temperature stress σ0 after heating and then cooling to the pouring temperature 0 =-380kPa,σ0 3 =-315kPa,σ0 5 =-204kPa,σ0 8 =-90kPa, corresponding stress reserve value ω σ 0 ,ω σ 3 ,ω σ 5 ,ω σ 8 Calculate them separately, as shown in formula (7):
[0111]
[0112] S7, such as Figure 7 As shown in the figure, based on the maximum compressive stress, room temperature stress, cracking stress and corresponding cracking time, stress reserve value and other indicators of the road base composed of circulating fluidized bed fly ash with different dosages in the expansion stage, the use environment and performance requirements of the road base are comprehensively considered to determine the dosage of circulating fluidized bed fly ash, balance the relationship between the compressive stress and cracking stress in the expansion stage, so that the shrinkage process is coordinated after the addition of circulating fluidized bed fly ash, and the purpose of "near zero" cracking of the road base material is achieved.
[0113] Finally, it should be noted that the above embodiments do not limit the present invention in any form. For those skilled in the art, some modifications and improvements can be made to the present invention. Therefore, any modification or improvement made without departing from the spirit of the present invention belongs to the scope of protection claimed in the present invention.
Claims
1. A "near zero" cracking circulating fluidized bed fly ash-based road base material, characterized in that: The raw materials include the following components in parts by weight: 20-35 parts of red mud, 20-30 parts of ordinary fly ash, 5-10 parts of slaked lime, 30-50 parts of coal gangue aggregate, and 20-80 parts of circulating fluidized bed fly ash-based composite material.
2. The "near zero" cracking circulating fluidized bed fly ash-based road base material according to claim 1 is characterized in that: The preparation method of the circulating fluidized bed fly ash-based composite material is as follows: S1, adding circulating fluidized bed fly ash into an alkaline solution for impregnation treatment, followed by centrifugation, drying, and calcining in an air atmosphere to obtain pretreated fly ash; S2, dissolving calcium nitrate, aluminum nitrate and urea in water, mixing them evenly, then adding pretreated fly ash thereto, heating and stirring to react, and after the reaction is completed, filtering, washing and drying to obtain composite fly ash; S3, dispersing the composite fly ash in an ethanol aqueous solution, then adding vinyltrimethoxysilane thereto, stirring for 2-5 hours, and then filtering, washing, and drying to obtain a double-bond modified composite material; S4, dispersing the double-bond modified composite material in an organic solvent, then adding butadiene, styrene and benzoyl peroxide thereto, heating and stirring to react, and after the reaction is completed, filtering, washing and drying to obtain a circulating fluidized bed fly ash-based composite material.
3. The "near zero" cracking circulating fluidized bed fly ash-based road base material according to claim 2 is characterized in that: In step S1, the calcination temperature is 800-900°C, and the calcination time is 2-4h.
4. The "near zero" cracking circulating fluidized bed fly ash-based road base material according to claim 2 is characterized in that: In step S2, the mass ratio of calcium nitrate, aluminum nitrate, urea and pretreated fly ash is 3-5:2-4:6-8:10-15.
5. The "near zero" cracking circulating fluidized bed fly ash-based road base material according to claim 2 is characterized in that: In step S2, the temperature of the heating and stirring reaction is 70-85° C., and the time of the heating and stirring reaction is 12-18 h.
6. The "near zero" cracking circulating fluidized bed fly ash-based road base material according to claim 2 is characterized in that: In step S3, the mass ratio of composite fly ash to vinyltrimethoxysilane is 8-12:1-3.
7. The "near zero" cracking circulating fluidized bed fly ash-based road base material according to claim 2 is characterized in that: In step S4, the mass ratio of the double bond modified composite material, butadiene, styrene and benzoyl peroxide is 10-15:3-4:3-5:0.5-1.
8. The "near zero" cracking circulating fluidized bed fly ash-based road base material according to claim 2 is characterized in that: In step S4, the temperature of the heating and stirring reaction is 60-80° C., and the time of the heating and stirring reaction is 3-5 h.
9. A method for preparing a "near zero" cracking circulating fluidized bed fly ash-based road base material, characterized in that: The method comprises the following steps: placing red mud, ordinary fly ash, slaked lime, coal gangue aggregate and the "near-zero" cracking circulating fluidized bed fly ash-based composite material according to any one of claims 1 to 8 in a blast drying oven and drying to constant weight, passing through a 200-mesh sieve after ball milling, and then mixing the above raw materials evenly, subsequently adding water, stirring for 3 to 5 minutes, making a test piece, demolding with a demoulding machine, placing it in a curing box and curing it to a corresponding age, so as to obtain a circulating fluidized bed fly ash-based road base material.
10. A method for formula design of "near zero" cracking circulating fluidized bed fly ash-based road base material, characterized in that: The following steps are involved: 1) The total number of red mud, ordinary fly ash, slaked lime and coal gangue aggregate is 100 parts, and the circulating fluidized bed fly ash-based composite material according to any one of claims 1 to 8 is used as a variable, and four types of road base materials are configured, and the amounts of the circulating fluidized bed fly ash-based composite material are 0, 30, 50 and 80 parts, respectively, which are recorded as proportions M0, M3, M5 and M8; 2) Assemble two polyamide inner molds into a dumbbell-shaped cavity, cover the outside with four cast iron dumbbell-shaped outer molds, put the dumbbell-shaped cast iron pad into the bottom of the cavity after assembly, move the assembled test mold into an environmental box, the temperature of the environmental box is regulated by a temperature and humidity controller, load four types of road base materials, and maintain for 4 hours after static pressure molding, then remove the cast iron outer mold to obtain the test piece and the inner mold, and fix the polyamide inner bottom mold at both ends of the inner mold; 3) Fix the specimen and inner mold on the UTM testing machine in the vertical direction through the upper and lower clamps. The upper end of the UTM clamp is connected to the force sensor and displacement sensor to measure the displacement s of the specimen. i Heli F i To conduct real-time testing, the allowable displacement range s of the specimen, the set temperature and humidity of the environment T / ω, and the data collection time interval t are input into the computer program connected to the UTM; 4) Turn on the UTM test equipment and perform displacement i Heli F i Real-time testing, temperature and humidity T0 and ω i In real-time testing, when the real-time displacement monitored by the displacement sensor reaches the set value s, the UTM testing machine pulls the specimen back to its initial position, so that the deformation of the specimen remains at 0. i Calculate the real-time strain and accumulate it to obtain the cumulative strain ε of autogenous shrinkage and creep shrinkage ij , the calculation formula is as follows: i Calculate real-time stress σ i , the calculation formula is as follows: e ij =(s i +s·j) / L (1) s i =F i / S (2) Where j is the number of times the UTM testing machine stretches the specimen, L is the specimen length in m, and S is the cross-sectional area of the specimen in m 2 ; 5) The stress-strain results of the ratios M0, M3, M5 and M8 are statistically analyzed, and the stress is denoted as σ i 0 , σ i 3 , σ i 5 , σ i 8 , the accumulated strain is denoted as ε ij 0 , ε ij 3 , ε ij 5 , ε ij 8 , the stresses at cracking are σ c 0 , σ c 3 , σ c 5 , σ c 8 , the cracking time is t c 0 ,t c 3 ,t c 5 ,t c 8 The least square method is used to calculate the real-time stress σ before cracking of the road base after adding circulating fluidized bed fly ash-based composite materials with different dosages ω i and the accumulated strain ε ij , cracking stress after cracking σ c and cracking time t c , as shown in formulas (3) to (6), Where ω is the proportion of the circulating fluidized bed fly ash-based composite material to the total amount of red mud, ordinary fly ash, slaked lime and coal gangue aggregate; 6) Draw the curves l0, l3, l5, and l8 of the real-time stress-time variation of the M0, M3, M5, and M8 specimens; the maximum compressive stress in the expansion stage is σ s 0 , σ s 3 , σ s 5 , σ s 8 , after heating up and then cooling down to the pouring temperature, the room temperature stress σ0 0 ,σ0 3 ,σ0 5 ,σ0 8 , corresponding to the stress reserve value ω σ 0 ,ω σ 3 ,ω σ 5 ,ω σ 8 Calculate them separately, as shown in formula (7). The larger the value, the better the crack resistance of the road base material. 7) According to the maximum compressive stress, room temperature stress, cracking stress and corresponding cracking time, stress reserve value index of the road base composed of circulating fluidized bed fly ash-based composite materials in the expansion stage with different dosages, the dosage of circulating fluidized bed fly ash-based composite materials is determined in combination with the road base use environment and performance requirements.
Citation Information
Patent Citations
Circulating fluidized bed fly ash-based auxiliary cementing material, and preparation method and application thereof
CN110282888A
Modified circulating fluidized bed fly ash-based cementing material and preparation method thereof
CN113880467A
Red mud / coal gangue-based cementing material road base formula and preparation process
CN114656234A
High-durability high-crack-resistance quick-setting cement material and preparation method thereof
CN117567115A
Circulating fluidized bed fly ash-based cementing material, preparation method and formula design method
CN118561559A